Van Loon : popular historian, journalist, and FDR confidant - Minnen, Cornelis A. van (World of the Roosevelts., 2005)
This biography is an exciting and nuanced portrait of one of FDR's true and closest friends, a man deeply involved in American cultural life in the first half of the twentieth century.